2017
DOI: 10.1038/nature23304
|View full text |Cite
|
Sign up to set email alerts
|

Correction of aberrant growth preserves tissue homeostasis

Abstract: Cells in healthy tissues acquire mutations with surprising frequency. Many of these mutations are associated with abnormal cellular behaviours such as differentiation defects and hyperproliferation, yet fail to produce macroscopically detectable phenotypes1–3. It is currently unclear how the tissue remains phenotypically normal, despite the presence of these mutant cells. Here we use intravital imaging to track the fate of mouse skin epithelium burdened with varying numbers of activated Wnt/β-catenin stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 35 publications
6
126
0
Order By: Relevance
“…Importantly, ~80% of Ras V12 cell clones are apically extruded/extruding in mouse intestine (Kon et al, 2017), suggesting that competition-mediated extrusion may play an important role in vivo . Supporting this, in the mouse hair follicle stem cell niche, activation of oncogenic HRas in specific clones triggers a competition-like interaction wherein WT cells ultimately surround and expel oncogenic outgrowths into the dermis (Brown et al, 2017). …”
Section: Cell Competition and The Active Extrusion Of Aberrant Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, ~80% of Ras V12 cell clones are apically extruded/extruding in mouse intestine (Kon et al, 2017), suggesting that competition-mediated extrusion may play an important role in vivo . Supporting this, in the mouse hair follicle stem cell niche, activation of oncogenic HRas in specific clones triggers a competition-like interaction wherein WT cells ultimately surround and expel oncogenic outgrowths into the dermis (Brown et al, 2017). …”
Section: Cell Competition and The Active Extrusion Of Aberrant Cellsmentioning
confidence: 99%
“…Importantly, although the resulting esophagi composed entirely of Notch-inhibited winner cells are morphologically normal, they are primed for tumorigenesis and permit p53-stabilized overgrowths (Alcolea et al, 2014). Although these examples did not monitor cell extrusion, observations of cell extrusion during the competitive removal of oncogenic cells in mouse hair follicles (Brown et al, 2017) and intestines (Kon et al, 2017) make more plausible a role for vertebrate competition-mediated cell extrusion in tumorigenesis.…”
Section: A Force For Evil: Cell Extrusion In Diseasementioning
confidence: 99%
“…However, this visualization method has a limited ability to identify dynamic and quickly resolved cell behaviors such as migratory bursts, cell shape changes, orientations of cell divisions, and apoptosis. Long-term, live imaging can capture these dynamic events and has improved understanding of development, homeostasis, and intrinsic responses to insults by stem cell populations [9, 10]. Challenges to real-time studies of skeletal regeneration include tissue depth, complexity, and relatively slow rates of regeneration that may require continuous live imaging over days.…”
Section: Introductionmentioning
confidence: 99%
“…28 Most of these clones will never develop into a skin cancer; animal studies show that normal (non-mutated) cells in the epidermis actively eliminate mutated cells, replacing the clones with normal skin architecture. 29 In addition, a recent laboratory study showed that regular (3 times per week) low dose, non-sunburning (1.3 SED) UV irradiation over 6 weeks was not associated with cumulative DNA damage, as demonstrated by the lack of accumulation of cyclobutane pyrimidine dimers in skin biopsies. 30 The accumulation of DNA damage depends on the extent of the damage (a function of the dose of UV radiation and the individual susceptibility) and capacity to eliminate mutated cells or repair DNA (there is some evidence that the latter is impaired by UVA irradiation, at least in laboratory studies).…”
Section: Biological Effects Of Uvb and Uvamentioning
confidence: 99%